2016
DOI: 10.1038/srep37835
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor Agonism Promotes Mechanical Allodynia After Priming the Nociceptive System with Capsaicin

Abstract: Sigma-1 receptor antagonists promote antinociception in several models of pain, but the effects of sigma-1 agonists on nociception (particularly when the nociceptive system is primed) are not so well characterized; therefore we evaluated the effects of sigma-1 agonists on pain under different experimental conditions. The systemic administration of the selective sigma-1 agonists (+)-pentazocine and PRE-084, as well as the nonselective sigma-1 agonist carbetapentane (used clinically as an antitussive drug), did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Such compounds include (+)-pentazocine, (+)-SKF10,047, SA4503 (1-[2-(3,4-dimethoxyphenyl)ethyl]-4-(3-phenylpropyl)piperazine), and PRE-084 (2-morpholin-4-ylethyl 1-phenylcyclohexane-1-carboxylate) [14]. Since the Sig-1R ligand PRE-084 shows various activities in the central nervous system in animal models, such as nootropic and antidepressant activities [43], we included this compound in some of the flux assays as control. Interestingly, we found that PRE-084 also promotes autophagic activity in HeLa cells; PRE-084 induces the autophagic flux comparable to ANAVEX2-73: at 1 μM an over 1,5-fold induction of the autophagic flux was observed (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Such compounds include (+)-pentazocine, (+)-SKF10,047, SA4503 (1-[2-(3,4-dimethoxyphenyl)ethyl]-4-(3-phenylpropyl)piperazine), and PRE-084 (2-morpholin-4-ylethyl 1-phenylcyclohexane-1-carboxylate) [14]. Since the Sig-1R ligand PRE-084 shows various activities in the central nervous system in animal models, such as nootropic and antidepressant activities [43], we included this compound in some of the flux assays as control. Interestingly, we found that PRE-084 also promotes autophagic activity in HeLa cells; PRE-084 induces the autophagic flux comparable to ANAVEX2-73: at 1 μM an over 1,5-fold induction of the autophagic flux was observed (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…In a series of studies of the effects on mechanical allodynia of Sig-1R agonists under control conditions and with pretreatment with capsaicin, Entrena et al (31,33) found that Sig-1R agonists did not alter sensitivity to mechanical stimulation under baseline conditions, and mechanical allodynia was present only when the system was pretreated with capsaicin. These effects were reversed by Sig-1R antagonists and absent in Sig-1R-knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonism of Sig-1R. Given that Sig-1R has been associated with capsaicin-induced mechanical hypersensitivity (31,33), we first tested whether these effects, which had not been directly linked to changes in TRPV1 activity or expression, can be explained by a role of Sig-1R on TRPV1-mediated pain processes.…”
Section: Pain-related Behavior In Response To Capsaicin Is Diminishedmentioning
confidence: 99%
“…S1R is reported in the trigeminal ganglia of male mice (Yoon et al, 2015), but expression in female trigeminal sensory neurons currently unknown. Activation of S1R elicits nociceptive responses, which can be reversed with SR1 antagonists (Kim et al, 2008;Gris et al, 2014;Parenti et al, 2014;Pyun et al, 2014;Roh and Yoon, 2014;Tejada et al, 2014;Entrena et al, 2016) or in S1R knockout mice (Entrena et al, 2009;de la Puente et al, 2009). Progesterone is a potent S1R antagonist (Johannessen et al, 2011;Zamanillo et al, 2013) and can inhibit nociception (Maurice et al, 2001;Ueda et al, 2001;Maurice and Su, 2009).…”
Section: Discussionmentioning
confidence: 99%